The Art in Science of MicroTAS 2019. Issue 15 (14th July 2020) - Cooksey, Gregory A.
Abstract : Greg Cooksey (left) and Maria Southall (right) present the Art in Science award to winner Joseph de Rutte at the RSC booth.